The Relationship Between Family Smoking Habits and Household Sanitation with the Incidence of Underweight in Children Aged 24-59 Months Systematic Review - Restuani Budiarti; Elvi Sunarsih; Nur Alam Fajar (GLOBAL HEALTH SCIENCE GROUP, 2026)
Underweight among children aged 24-59 months is a key indicator of malnutrition and remains a public health issue in Indonesia. Various factors contribute to underweight, including household smoking habits and sanitation conditions. Exposure to cigarette smoke indoors increases the risk of acute respiratory infections (ARI), leading to nutritional deficiencies and impaired growth in children. Additionally, poor sanitation particularly limited access to clean water and inadequate toilet facilities contributes to a higher incidence of diarrheal diseases, which directly affect weight loss in children. This study uses a systematic review method, which aims to analyze the relationship between smoking habits in the home and household sanitation with the incidence of underweight in children aged 24-59 months. The systematic review was conducted by examining 30 scientific journals discussing risk factors for underweight in children, particularly those related to smoking habits in the home and sanitation conditions. The analyzed journals were obtained from various academic databases such as Google Scholar, PubMed, ScienceDirect, and SINTA (Science and Technology Index), with a publication period between 2013-2024.The findings indicate that children living in homes with smoking family members are more likely to experience underweight compared to those in smoke-free environments.